[Houses on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of houses on Heimaey. White and yellow houses with blue or red roofs cover the photograph. Green yards and grey, stone paths surround the houses. Eldfell is visible in the background, towering over the buildings from behind a grey cloud.